The Synergistic Combination of Cisplatin and Piperine Induces Apoptosis in MCF-7 Cell Line - Abolfazl Fattah; Ali Morovati; Zahra Niknam; Ladan Mashouri; Amirhooman Asadi; Shirin Tvangar Rizi; Mojtaba Abbasi; Fatemeh Shakeri; Omid Abazari (Tehran University of Medical Sciences, 2021)
Background: Piperine is a natural compound obtained from the Piper nigrum that exhibits anti-proliferative and anti-cancer activity in cancer cell lines. We analyzed the cytotoxic effect of piperine combined with cisplatin compound in the human MCF-7 breast cancer cell line and the underlying mechanism. Methods: The present in vitro study was performed on MCF-7 cell line in Jahrom University of Medical Sciences between, Jahrom, Iran from 2016 to 2017. Cultured MCF-7 cells were seeded into four groups: a control group (untreated group), a group treated with cisplatin, a group treated with piperine and a group treated with cisplatin and piperine. Cell viability was analyzed using the MTT assay method. Flow c-ytometric analysis was investigated for apoptosis. The mRNA and protein expression of the apoptotic regulators p53, Bcl-2, Bax, caspase 3 and caspase 9 were detected by quantitative real-time polymerase chain reaction (qRT-PCR) and western blotting analysis. Results: Piperine (20 and 30 µM) in combination with cisplatin (5, 10 and 15 µM) for 24 h synergistically inhibited cell viability of MCF-7 breast cancer cells more than piperine and cisplatin used alone. Synergistic anti-breast cancer activities cisplatin (5 µM) and piperine (20 µM) were via inducing apoptosis. Piperine (20 µM) and cisplatin (5 µM) for 24 h induce apoptosis strongly through reduction of Bcl-2 and increase of caspase 3, p53, caspase 9, and Bax. Conclusion: Piperine in combination with cisplatin could trigger p53-mediated apoptosis more effective than cisplatin alone in MCF-7 breast cancer cells, reducing the toxic dose of cisplatin used in cancer chemotherapy.